Case Report: Simultaneous Ascending Aortic Dissection and Pulmonary Artery Dissection Combined by Aortopulmonary Fistula After Aortic Valve Replacement - Lihui Song (Frontiers Media S.A., 2021)
Aortopulmonary fistula with/without pulmonary artery dissection is an extremely rare and fatal complication of acute aortic dissection and is often discovered postmortem. We present a case with a simultaneous ascending aortic dissection and pulmonary artery dissection combined by aortopulmonary fistula after aortic valve surgery. However, the patient died of postoperative complications after surgery. Herein, the anatomical basis for this rare entity and its outcome is explored with an emphasis.